Tobin’s Q Ratio Sebagai Alat Ukur Nilai Perusahan Bank Syariah - Sisca Mediyanti; Emilda Kadriyani; Fani Sartika; Intan Novia Astuti; Eliana Eliana; Wardayani Wardayani (Universitas Negeri Medan, 2021)
Firm value is a measure of the success of management in managing company assets. Every shareholder always hopes that every fund invested can contribute to their prosperity. Through the measurement of company value, it will be known the success of the management in meeting the expectations of shareholders. This study aims to determine the value of Islamic banking companies in Indonesia that have sold their shares to the public (go public). The number of samples is 3 (three), Islamic Banks, with a data observation period starting from 2018 to 2020. Secondary data were obtained through the websites www.idx.co.id and www.idnfinancials.com, the data analysis method used was quantitative descriptive. The conclusion that can be drawn is that the company value of Islamic banks has a good ratio, it is known that the Tobin's Q ratio of all Islamic banks is greater than 1 in the 2018-2020 period, which means that management can manage company assets well and can meet shareholders expectations. In general, the performance of Islamic banks in Indonesia has increased which is known from the average Tobin's Q ratio which increases every year, so it is known that the company's management performance is getting more optimal.